Covalent-organic framework based Z-scheme heterostructured noble-metal-free photocatalysts for visible-light-driven hydrogen evolution. Issue 8 (10th February 2020) - Zhang, Yang-Peng; Tang, Hong-Liang; Dong, Hong; Gao, Meng-Yao; Li, Chang-Cheng; Sun, Xiao-Jun; Wei, Jin-Zhi; Qu, Yang; Li, Zhi-Jun; Zhang, Feng-Ming
Abstract : A COF-based Z-scheme heterostructure hybrids (α-Fe2 O3 /TpPa-2-COF) for noble-metal-free photocatalytic hydrogen evolution. Abstract : The construction of a Z-scheme heterostructured system is an effective way to improve the separation of photogenerated electrons–holes and the hydrogen evolution activity of photocatalysts. In this work, for the first time, we report a class of covalent-organic framework (COF) based Z-scheme heterostructured hybrids for efficient visible-light-driven photocatalytic hydrogen evolution. An excellent visible-light harvesting COF, TpPa-2-COF, was chosen to integrate with α-Fe2 O3 for the construction of Z-scheme hybrids. As a result, the α-Fe2 O3 /TpPa-2-COF (3 : 7) hybrid material shows an optimal hydrogen evolution rate of 3.77 mmol h −1 g −1 without the participation of any noble metal co-catalyst. This hydrogen evolution rate is about 53 times higher than that of the parent TpPa-2-COF under the same conditions and comparable to that with a Pt (2 wt%) co-catalyst. Further investigations confirm that the tight integration of α-Fe2 O3 and 2D COFs can effectively promote the transfer of photogenerated electrons from the CB of α-Fe2 O3 to the VB of COFs thus leading to an efficient separation of photogenerated charges of the COF and a greatly enhanced photoactivity. Considering the first report of the COF-based Z-scheme heterostructure as a noble-metal-free photocatalyst for efficient hydrogen evolution, this work may open a new pathway for the further design and synthesis of COF-based hybrid photocatalysts for efficient H2 evolution.